Research on Street Characteristics Inside and Outside Cuiwei Village in Qianshan, Zhuhai Based on Depthmap - Junzhang Chen (Formosa Journal of Sustainable Research, 2022)
Based on the Cuiwei historical village in Qianshan District of Zhuhai, this study studies the street space inside and outside the village block. With the help of Depthmap and SPSS software, the complex Street axis space is quantitatively analyzed, including the analysis of synergy, spatial form and vitality, pedestrian interface and symbiosis, traffic flow correlation, topological depth and street spatial correlation. Draw relevant conclusions according to the analysis results. In order to provide reference and reference for government management personnel.